Evaluation of physiological changes and therapeutic approaches of hypertension in pregnancy - Rahman, Mohammed Safi Ur-; Sumayya; Ayesha Naseer; Korapati Ramarao; Nayak, P Srinivas (Journal of Biomedical and Pharmaceutical Research, 2020)
There are various physiological and pharmacokinetic changes occur in pregnancy to nurture the developing foetus, avoid toxicities, resistance to infections and prepare the mother for labour and delivery. Some of these changes influence normal biochemical values while others may mimic symptoms of medical disease and alter the kinetic parameters of the drugs. It is important to differentiate between normal physiological changes and disease pathology. This article highlights the important changes that take place during normal pregnancy, development of common conditions and pharmacokinetic variations. This review also will describe basic concepts in pharmacokinetics and their clinical relevance and highlight the variations in pregnancy that may impact the pharmacokinetic properties of medications, different treatment approaches, contraindications and drugs used in pregnancy Key words: Physiological changes in pregnancy, Hypertension, pregnancy disorders.